2021
DOI: 10.1039/d1na00175b
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the nanoscale effects of charge traps on electrical transport in grain structures of indium tin oxide thin films

Abstract: We report the mapping of the nanoscale effects of charge trap activities in the grain structures of an oxygen plasma−treated Indium tin oxide (ITO) thin film. Here, a conducting Pt...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(110 reference statements)
1
5
0
Order By: Relevance
“…This clearly explains the small contribution of grain boundary scattering (by carrier scattering at {101} CSPs). The results of the fits are in the similar range (∼10 13 cm −2 ) as the experimental data measured by Jeon et al on In-doped SnO 2 (ITO) sample [24].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This clearly explains the small contribution of grain boundary scattering (by carrier scattering at {101} CSPs). The results of the fits are in the similar range (∼10 13 cm −2 ) as the experimental data measured by Jeon et al on In-doped SnO 2 (ITO) sample [24].…”
Section: Resultssupporting
confidence: 81%
“…Thus the dependence μ(n) strongly depends on the trap density at grain boundaries, which in turn depends on the deposition conditions such as oxygen partial pressure, temperature, or post-deposition treatment. For instance, Jeon et al have examined the impact of charge trap activities on electron transport within the grain structures of an In doped SnO 2 (ITO) thin film treated with oxygen plasma and revealed that the regions at the boundaries of the grains had a higher density of charge traps and thus a lower conductance compared to the areas inside the grains of the thin film [24]. 8.17 The authors also estimated the trap density at ITO grain boundaries at about 3 × 10 13 cm −2 .…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the Au-ITO heterojunction as a result of the plasma treatment, as well as the difference in the Fermi levels of Au and ITO, facilitates the transfer of excess plasma electrons from Au to ITO, thereby preventing the structural deformation of the AuNRs. Besides that, oxygen plasma treatment increases the conductivity of ITO by removing carbon contaminants, thus inducing surface dipole formation and increasing the charge carrier density of the ITO substrate. , These may result in increased work function of ITO, therefore enhancing the high-energy electrons transferred to ITO without damaging the AuNR structure. Since the transmittance spectra of untreated and various time oxygen plasma-treated ITO substrates (Figure S6A,B) do not show a significant difference, the increased work function of the ITO substrate due to plasma treatment may have little or negligible impact on the LSPR spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Besides that, oxygen plasma treatment increases the conductivity of ITO by removing carbon contaminants, thus inducing surface dipole formation and increasing the charge carrier density of the ITO substrate. 29,30 These may result in increased work function of ITO, 30−32 therefore enhancing the high-energy electrons transferred to ITO without damaging the AuNR structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation